Impact of Mid-Luteal Phase GnRH Agonist Administration on Reproductive Outcomes in GnRH Agonist-Triggered Cycles: A Randomized Controlled Trial - Benmachiche, Abdelhamid; Benbouhedja, Sebti; Zoghmar, Abdelali; Boularak, Amel; Humaidan, Peter (Frontiers in Endocrinology, 2017)
Objective To explore whether the addition of a mid-luteal bolus of GnRH agonist (GnRHa) improves the implantation rate (IR) in in vitro fertilization (IVF) cycles. Design A randomized controlled trial. Setting Private IVF center. Patients 328 IVF/intracytoplasmic sperm injection patients were triggered with GnRHa and received 1,500 IU HCG on the day of oocyte pick-up (OPU) in addition to a standard luteal phase support (LPS). Intervention(s) In addition, the study group received a bolus of GnRHa 6 days after OPU, whereas the control group did not. Main outcome measure Implantation rate. Secondary outcome measure(s) Ongoing pregnancy (OP) and live birth (LB) rates. Results Although serum concentrations of FSH, LH, E2, and P on day OPU + 7 were significantly higher in the study group compared to the control group, the IR was not statistically different between the treatment group (27%) and the control group (23%) [odds ratio (OR) 1.2 (95% CI 0.9–1.7), P < 0.27]. Similarly, the OP rate was 37% in the treatment group and 31% in the control group [OR 1.3 (95% CI 0.8–2.0), P < 0.23]. The LB rate was 36% in the treatment group and 31% in the control group [OR: 1.3 (95% CI 0.8–2.0), P < 0.27]. Conclusion Although a trend toward a higher IR and pregnancy rate was observed in the treatment group, this difference was not statistically significant. However, the absolute risk difference of 5% found for LB is clinically relevant, warranting further investigation. NCT 02053779.